Problems And Challenges Of Attendance In Medical Students - Muhammad Khurram (Journal of Rawalpindi Medical College)
Completing essential training in Medicine, Surgery, Gynecology, and Pediatrics   during the final year of Medical College is crucial for individuals aspiring to become doctors. Medical training in Large Group Interactive Sessions and Clinical Clerkships is designed to equip students with knowledge, skills, and experience necessary to practice medicine safely and effectively.